Prevalence of somatic mitochondrial mutations and spatial distribution of mitochondria in non-small cell lung cancer - Kazdal, Daniel; Harms, Alexander; Endris, Volker; Penzel, Roland; Kriegsmann, Mark; Eichhorn, Florian; Muley, Thomas; Stenzinger, Albrecht; Pfarr, Nicole; Weichert, Wilko; Warth, Arne (British journal of cancer, 2017)
Background:Mitochondria are considered relevant players in many tumour entities and first data indicate beneficial effects of mitochondria-targeted antioxidants in both cancer prevention and anticancer therapies. To further dissect the potential roles of mitochondria in NSCLC we comprehensively analysed somatic mitochondrial mutations, determined the spatial distribution of mitochondrial DNA within complete tumour sections and investigated the mitochondrial load in a large-scale approach.Methods:Whole mitochondrial genome sequencing of 26 matched tumour and non-neoplastic tissue samples extended by reviewing published data of 326 cases. Systematical stepwise real-time PCR quantification of mitochondrial DNA covering 16 whole surgical tumour sections. Immunohistochemical determination of the mitochondrial load in 171 adenocarcinoma and 145 squamous cell carcinoma.Results:Our results demonstrate very low recurrences (max. 1.7%) and a broad distribution of 456 different somatic mitochondrial mutations. Large inter- and intra-tumour heterogeneity were seen for mitochondrial DNA copy numbers in conjunction with a correlation to the predominant histological growth pattern. Furthermore, tumour cells had significantly higher mitochondrial level compared to adjacent stroma, whereas differences between tumour entities were negligible.Conclusions:Non-evident somatic mitochondrial mutations and highly varying mitochondrial DNA level delineate challenges for the approach of mitochondria-targeted anticancer therapies in NSCLC.
Published online 30 May 2017
Gesehen am 31.07.2018